Application of spatial transcriptomics analysis using the Visium system for the mouse nasal cavity after intranasal vaccination - Toyama, Sakiko; Honda, Tomoko; Iwabuchi, Sadahiro; Hashimoto, Shinichi; Yamaji, Kenzaburo; Tokunaga, Yuko; Matsumoto, Yusuke; Kawaji, Hideya; Miyazaki, Takashi; Kikkawa, Yoshiaki; Kohara, Michinori (Frontiers in Immunology, 2023)
This is a provisional file, not the final typeset article Intranasal vaccines that elicit mucosal immunity are deemed effective against respiratory tract infections such as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), but their ability to induce humoral immunity characterized by immunoglobulin A (IgA) and IgG production is low. It has been reported that vaccination with a mixture of a viscous base carboxyvinyl polymer (CVP) and viral antigens induced robust systemic and mucosal immune responses. In this study, we analyzed the behavior of immunocompetent cells in the nasal cavity over time by spatial transcriptome profiling induced immediately after antigen vaccination using CVP. We established a method for performing spatial transcriptomics using the Visium system in the mouse nasal cavity and analyzed gene expression profiles within the nasal cavity after intranasal vaccination.Glycoprotein 2 (Gp2)-, SRY-box transcription factor 8 (Sox8)-, or Spi-B transcription factor (Spib)-expressing cells were increased in the nasal passage (NP) region at 3-6 hr after SARS-CoV-2 spike protein and CVP (S-CVP) vaccination. The results suggested that microfold (M) cells are activated within a short period of time (3-6 hr). Subsequent cluster analysis of cells in the nasal cavity showed an increase in Cluster 9 at 3-6 hr after intranasal vaccination with the S-CVP. We found that Il6 in Cluster 9 had the highest log2 fold values within the NP at 3-6 hr. A search for gene expression patterns similar to that of Il6 revealed that the log2 fold values of Edn2, Ccl20, and Hk2 also increased in the nasal cavity after 3-6 hr. The results showed that the early response of immune cells occurred immediately after intranasal vaccination.In this study, we identified changes in gene expression that contribute to the activation of M cells and immunocompetent cells after intranasal vaccination of mice with antigen-CVP using a timeseries analysis of spatial transcriptomics data. The results facilitated the identification of the cell types that are activated during the initial induction of nasal mucosal immunity.